THE ACCEPTANCE AND USE OF WHATSAPP MOBILE INSTANT MESSAGING FOR LEARNING SUPPORT - Alias bin Deraman; Mohd Shukor bin Abd Rahman (Journal of Islamic, Social, Economics and Development, 2023)
This study is based on the previous work that had done by So, S. (2016) at a university in Hong Kong with three main research’s objective including test the performance of WhatsApp acceptance, determine of the main predictor of change, and establish and testing model of acceptance and use. The performance was measure by given the academic pre-test and post-test both to the experiment and control group of students. Besides the traditional classroom learning for both groups, the experimental group was also supported with softcopy materials and the interaction via WhatsApp outside face-to-face hours. Meanwhile, the participants of the control group used WhatsApp only for academic communication. Pre-test scores were used as the covariate. The marginal means on the post-test scores showed that the participants in the experimental group performed better than those in the control group. The intervention of WhatsApp improved the learning achievement of the participants. The determination of main predictor of change was identify by performing the Principal Component Analysis (PCA) to the sub divided of WATQL provided by So, S. (2016) which classified 4 main component including Perceived of Usefulness (PU), Perceived Ease of Use (PEOU) and Effort Expectancy (EE) as Independent Variable (IV) and acceptance of WhatsApp for learning support (ACCEPTANCE) as dependent variable (DV). The questionnaire was administered at the end of the study by given the Google Form link through CSC134 students WhatsApp group in volunteer mode. The Multiple Linear Regression (MLR) analysis had used to do the hypothesis testing, which found that there were exist enough evidence to conclude that all the IV components were predicting the DV, therefore the model is accepted and useful to predict the acceptance and used of WhatsApp to support learning.